2021
DOI: 10.1021/acscatal.1c01685
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Reducibility of the Ceria–Tin Oxide Solid Solution Modifies the CO Oxidation Mechanism at the Platinum–Oxide Interface

Abstract: Many important catalytic reactions take place at metal−oxide interfaces. However, their mechanisms are typically difficult to probe due to the low concentration of active sites and the lack of highly sensitive spectroscopic methods. In this work, we analyze the impact of oxide reducibility on the mechanism of low-temperature CO oxidation over platinum nanoparticles supported on ceriabased solid solutions. We demonstrate that the easier reducibility of Ce 4+ at the Pt/ Ce 0.5 Sn 0.5 O 2 interface (in comparison… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…1,2 Platinum supported on transition-metal oxides, in particular, is employed to promote a variety of chemical processes, such as oxidation and reduction reactions in proton-exchange membrane fuel cells, 3,4 oxidation of hydrocarbons, 5 and the treatment of exhaust gases. 6,7 The interaction of gas-phase oxygen with bulk Pt has been studied in great detail, both experimentally 8,9 and theoretically. 10,11 Pt, however, is often used in the form of nanoparticles (NPs) to take advantage of their high surface-to-volume ratio and to optimize the use of this rare and expensive element.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Platinum supported on transition-metal oxides, in particular, is employed to promote a variety of chemical processes, such as oxidation and reduction reactions in proton-exchange membrane fuel cells, 3,4 oxidation of hydrocarbons, 5 and the treatment of exhaust gases. 6,7 The interaction of gas-phase oxygen with bulk Pt has been studied in great detail, both experimentally 8,9 and theoretically. 10,11 Pt, however, is often used in the form of nanoparticles (NPs) to take advantage of their high surface-to-volume ratio and to optimize the use of this rare and expensive element.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Heterogeneous catalysts, often in the form of metal particles supported on oxides, play an important role in many industrial chemical processes and in environmental protection. , Platinum supported on transition-metal oxides, in particular, is employed to promote a variety of chemical processes, such as oxidation and reduction reactions in proton-exchange membrane fuel cells, , oxidation of hydrocarbons, and the treatment of exhaust gases. , The interaction of gas-phase oxygen with bulk Pt has been studied in great detail, both experimentally , and theoretically. , Pt, however, is often used in the form of nanoparticles (NPs) to take advantage of their high surface-to-volume ratio and to optimize the use of this rare and expensive element. Similar to bulk Pt, there have been works investigating the oxidation of Pt NPs in catalytic conditions. , Because the oxidation state of Pt NPs has a strong impact on their catalytic properties, , it is crucial to understand how different factors such as size of NPs, interaction of NPs with the support, and conditions of the gas-phase atmosphere affect the propensity of Pt NPs to be oxidized.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, we demonstrated that operando quick XAS combined with a transient experimental strategy provides quantitative information on the redox activity of metal centers involved in the Mars-van Krevelen mechanism of carbon monoxide and ethanol oxidation on various catalysts. [28][29][30][31][32] In particular, for the bilayered VOx/TiOx/SiO2 catalyst, we have shown that V 5+ to V 4+ reduction upon ethanol oxidation is kinetically coupled with acetaldehyde formation, while the redox activity of titanium was shown to be not directly involved in the catalytic cycle. [32] In this work, we applied the same transient XAS methodology to uncover the redox processes involved in ethanol ODH over VOx/CeO2 catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Metal nanoparticles (NPs) have been studied as efficient catalysts owing to their wide applications in the pharmaceutical industry, production of fine chemicals, biology, CO 2 reduction, CO oxidation, selective hydrogenation, and C-C cross-coupling. [1][2][3][4][5][6] The dispersion of gold (Au) NPs remained stable for several months. Au NPs with large surface areas can act as heterogeneous catalysts with high reactivity and high selectivity, [7,8] and they can be recycled without any loss of catalytic activity.…”
Section: Introductionmentioning
confidence: 99%